1980
DOI: 10.1346/ccmn.1980.0280207
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbed Cr(III) on Chlorite, Illite, and Kaolinite: An X-Ray Photoelectron Spectroscopic Study

Abstract: The adsorption of Cr(III) was studied at pH 1, 2, 3, 4, 6, 8, and 10 on chlorite and kaolinite and at pH l, 2, 3, and 6 on illite. The amount of chromium adsorbed on chlorite varied from 3.1 • l0 -5 mole/ g at pH 1 to 16.6 • 10 -3 mole/g at pH 4, and on illite from 4.9 • 10 -5 mole/g to 9.2 • 10 5 mole/g at pH 1 and 3, respectively. Kaolinite adsorbed 3.7 • 10 -5 mole Cr/g at pH 1, 2, and 3 and 5.5 • 10 -5 mole Cr/ g at pH 4. Measurements of the Cr 2p core-level binding energies indicate that chromium is proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…In all sorption samples, a low degree of distortion around sorbed Co is indicated by EXAFS analysis o f the ligating oxygen shell and by the small amplitude of pre-edge feature in the X-ray abs o r p t i o n edges, similar to that o f Co in both Co(NO3)2(aq) and Co(OH)2(s ). The XAS results are in agreement with XPS studies of metal ions on clays that indicate a local electronic environment similar to aquo solution complexes Dillard, 1975, 1977;Koppelman et al, 1980;Dillard and Koppelman, 1982;Schenk et al, 1983). In the lowest uptake samples, backscattering from A1/Si is weak and variable among the different kaolinite samples.…”
Section: Types Of Surface Complexes On Kaolinitesupporting
confidence: 84%
See 1 more Smart Citation
“…In all sorption samples, a low degree of distortion around sorbed Co is indicated by EXAFS analysis o f the ligating oxygen shell and by the small amplitude of pre-edge feature in the X-ray abs o r p t i o n edges, similar to that o f Co in both Co(NO3)2(aq) and Co(OH)2(s ). The XAS results are in agreement with XPS studies of metal ions on clays that indicate a local electronic environment similar to aquo solution complexes Dillard, 1975, 1977;Koppelman et al, 1980;Dillard and Koppelman, 1982;Schenk et al, 1983). In the lowest uptake samples, backscattering from A1/Si is weak and variable among the different kaolinite samples.…”
Section: Types Of Surface Complexes On Kaolinitesupporting
confidence: 84%
“…In a series of investigations, metal ions (Co(II), Ni(II), Cr(III), Fe(III)) sorbed to clays and oxides (kaolinite, illite, chlorite, goethite) as a function of increasing pH were studied by XPS Dillard, 1975, 1977;Koppelman et al, 1980;Dillard and Koppelman, 1982;Schenk et al, 1983). Based on changes in binding energies and peak intensities, these studies concluded that the bonding environment of the metal cation becomes "more ionic" with increasing pH.…”
Section: Spectroscopic Studies Of Sorbed Metal Ionsmentioning
confidence: 99%
“…The measured binding energy (BE) for the Cr 2p3/2 level of each chromium complex-clay sample is 577.3 -+ (Table 3) for chromium complexes adsorbed on the three clays are equal, within experimental error, to the Cr 2p binding energies for adsorbed chromium aqua ions (Koppelman et al, 1980). In addition, the N/Cr atom ratio is less than that expected if the complexes were adsorbed as Cr(NH3)~ 3+ or Cr(en)33+.…”
Section: Xps Measurementsmentioning
confidence: 88%
“…It is not likely that Cr(III) is reduced to Cr(II). The equivalence of the binding energies for adsorbed Cr(H.zO)n 3+ (Koppelman et al, 1980) and the hydrolysis products of Cr(en)33+ and Cr(NH3), 3+ suggests that the hydrolysis products are Cr(III) species. Of particular significance is the fact that for Cr(NH3)~ 3+ adsorption, the change in pH is greatest and fastest for chlorite and illite and slowest for kaolinite.…”
Section: Xps Measurementsmentioning
confidence: 99%
“…Many studies of the interactions between radionuclides and dierent mineral matrices have used this powerful tool *To whom all correspondence should be addressed. (Koppelman et al, 1980;Dillard and Koppelman, 1992). In this study the sorption anities of magnesite towards cesium and barium ions are examined.…”
Section: Introductionmentioning
confidence: 99%